Elaboração de um dicionário karo-português - Araújo, Fernanda Oliveira de (Museu Paraense Emílio Goeldi, 2023)
The Karo language, spoken by the Arara Indians of Rondônia, is the only representative language of the Ramarama linguistic family (Gabas, 2000), a Tupi trunk (Rodrigues, 1964). This language is at risk of extinction because it is spoken by a small number of indigenous people, about 150 individuals. Aware of this situation, the Arara demand that the results of research projects carried out on their language be brought back to the community in a practical way that will benefit them. Building a dictionary is one of these demands. The present subproject consists of the creation of a Karo-Portuguese dictionary that will not only bring back to the Arara community practical results of research projects in their language, but will also provide access to written material in that language. The Karo-Portuguese dictionary is important to ensure written records in the language and can help the Indians in the education process to learn Karo orthography. In the first phase of the implementation of this subproject, the Toolbox software was chosen, and a special font (Karo Times New Roman) was created for use in the Karo language database entries. The data are original data, and were collected by the researcher Nilson Gabas, Jr. and Sebastião Arara. The input of lexical items into the database required the definition of eleven input fields, which we intend to present and justify. Several lexical items of all Karo word classes were entered into the database, such as: verbs (transitive and intransitive), adjectives, nouns (alienable and inalienable), ideophones, particles, and conjunctions.